Sweden now 1980-II_5 - Testologen Ltd. (IMU-Testologen AB, 1985)
A major part of this survey is a replication of earlier surveys. Questions about life style and decisional power at work are back again after being removed the year before. New questions deals with how much of the content the respondent reads in different papers

Purpose:

Collect broad information about interests, purchasing habits and media choices

A major part of this survey is a replication of earlier surveys. Questions about life style and decisional power at work are back again after being removed the year before. New questions deals with how much of the content the respondent reads in different papers

Syfte:

Samla in en bred information om intressen, köpvanor och mediaval

Subset of Sweden now 1980-II, covering the period 1980-05-08 to 1980-06-19.
ORVESTO 1980-II_5
Sverige nu 1980-II
Keywords: newspaper readership; tidnings läsekrets; periodicals readership; tidskrifts läsekrets; domestic appliances; hushållsapparat; consumer goods; konsumtionsvaror; interest (cognitive processes); intresse (kognitiva processer); frequency; frekvens; Consumption and consumer behaviour; Konsumtion och konsumentbeteende; Media; Media; Public relations; Public relations; Social Sciences; Samhällsvetenskap; Media and Communication Studies; Medie- och kommunikationsvetenskap